Maintenance of haemocytes of edible oyster, Crassostrea madrasensis (Preston) in artificial media - Ittoop, Gijo; George, K C; Sanil, N K; Shobhana, K S; Nisha, P C (Indian Journal of Fisheries, 2011)
The haemocytes of Crassostrea madrasensis were maintained in Hank’s balanced salt solution (HBSS), HBSS with 10% foetal calf serum (FCS), tissue culture media M 199, and M 199 with 10% FCS. Total counts of viable haemocytes were taken at 0 hr, 24 hrs, 48 hrs, and 72 hrs. HBSS and HBSS with 10% FCS were found to maintain cell viability upto 72 hrs without much reduction in the count of viable cells. In M199 and M199 with 10% FCS, it was found that a substantial increase of small hyalinocytes occurred at 24 hrs and 48 hrs. This was followed by a steep fall in the number of viable cells at 72 hrs in both the media. The HBSS, HBSS with 10% FCS, M199 and M199 with 10% FCS were found to be good for maintaining the cells in viable state. However, only M 199 and M 199 with 10% FCS indicated multiplication of haemocytes.